2007
DOI: 10.1086/513279
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Murine Model to Evaluate Topical Vaginal Microbicides: Mucosal Inflammation and Susceptibility to Genital Herpes as Surrogate Markers of Safety

Abstract: A critical gap in microbicide development is the absence of surrogate safety markers. The objective of the present study was to develop a murine model to examine the mucosal response to microbicides and to assess the functional implication of observed changes. Mice received 14 daily intravaginal doses of nonoxynol-9, PRO 2000, or placebo gel. Nonoxynol-9 induced an inflammatory response characterized by increases in levels of cytokines and chemokines, recruitment of neutrophils and monocytes into the genital t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
53
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 41 publications
10
53
2
Order By: Relevance
“…Numerous vaginal microbicides that have been tested in humans possess strong surfactant properties and, therefore, may also alter mucus pore size. However, most of these agents caused substantial toxicity to the vaginal epithelium by damaging cell membranes, and therefore failed to reduce (or in some cases even increased) infection rates (42)(43)(44)(45). Thus, whereas our results suggest that the use of surface-active agents may help limit infection by decreasing the flux of pathogens to the epithelium, this hypothesis can only be tested with agents that do not simultaneously compromise the epithelial cell layer.…”
Section: Discussionmentioning
confidence: 65%
“…Numerous vaginal microbicides that have been tested in humans possess strong surfactant properties and, therefore, may also alter mucus pore size. However, most of these agents caused substantial toxicity to the vaginal epithelium by damaging cell membranes, and therefore failed to reduce (or in some cases even increased) infection rates (42)(43)(44)(45). Thus, whereas our results suggest that the use of surface-active agents may help limit infection by decreasing the flux of pathogens to the epithelium, this hypothesis can only be tested with agents that do not simultaneously compromise the epithelial cell layer.…”
Section: Discussionmentioning
confidence: 65%
“…While N9, BZK, and SDS were selected as positive controls in models of vaginal irritation and inflammation, as reported in previous works (2,9,13,15,16), carboxymethyl cellulose (CMC; which is widely used as a microbicide excipient and control) and TFV (a microbicide candidate which is proven to be efficacious and safe [1]) were chosen as negative controls. N9 and TFV were purchased from LKT Laboratories, Inc., and Molekula Limited (United Kingdom), respectively.…”
Section: Reagentsmentioning
confidence: 99%
“…Specifically, N9 did not prevent HIV-1 infection when used at a low frequency, and it even increased the risk of HIV-1 infection by frequent use (42). A series of studies that followed found that genital inflammation and the disruption of the cervicovaginal epithelium induced by microbicides are critical risk factors associated with the incidence of HIV-1 infection (9,13,15,16,18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Progesterone is frequently used in vaginal infection models to synchronize estrous cycles and to increase susceptibility by thinning out the vaginal layer, including models of simian immunodeficiency virus/SHIV infection in nonhuman primates (13,14,67,69,70,78) and mouse models of HIV-1 (68,79), human papillomavirus (HPV) (80), and herpes simplex virus 2 (HSV-2) (81) infection. Increased susceptibility to viral infection after mucosal N-9 application has been described in models of HPV infection (80) and both vaginal and rectal HSV-2 infection (72,82,83). In addition, an increased frequency of HIV-1 infection has been found in female sex workers after application of high doses of N-9 (84).…”
Section: Discussionmentioning
confidence: 99%